2017
DOI: 10.21608/epx.2018.8950
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respirable particulates in two residential areas of Kuwait State during dusty and nondusty storms: A time-series comparative study

Abstract: Respirable particulate is slightly higher in Ali Sabah Al-Salem than in Mansoria. Days with dust storms have significantly greater PM10 levels than those without. The study recommends application of land-use planning, and windbreaks, combating desertification, and enhancing stoppage of outdoor activities during dust storms among public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…77 studies found which measured different pollutants indoor or/ and outdoors, where majority of these studies (59 studies) measured only outdoor pollutants (Abdul-Wahab et al, 1996, Al-Awadhi, 2016, Al-Awadhi, 2014, Al-Awadhi and Alshuaibi, 2013, Alet al, 2008a, Al-Dabbous and Kumar, 2014, Al-Dabbous and Kumar, 2015, Al-Dabbous et al, 2016, Aldaihani and Alenezi, 2017, Alenezi and Al-anezi, 2015, Al-Hurban and Al-Ostad, 2009, Alkandari and Moein, 2018, Alshammari, 2018, Al-Shammari, 2013, Bourasli, 2013, Bu-Olayan and Thomas, 2011, Bu-Olayan and Thomas, 2010b, Engelbrecht et al, 2009b, Kuśmierczyk-Michulec and Bourgouin, 2018, Li et al, 2020, Nasrallah et al, 2003, Yassin, 2011, Yassin et al, 2018a, Zaki et al, 2017.…”
Section: Non-epidemiological Studiesmentioning
confidence: 99%
“…77 studies found which measured different pollutants indoor or/ and outdoors, where majority of these studies (59 studies) measured only outdoor pollutants (Abdul-Wahab et al, 1996, Al-Awadhi, 2016, Al-Awadhi, 2014, Al-Awadhi and Alshuaibi, 2013, Alet al, 2008a, Al-Dabbous and Kumar, 2014, Al-Dabbous and Kumar, 2015, Al-Dabbous et al, 2016, Aldaihani and Alenezi, 2017, Alenezi and Al-anezi, 2015, Al-Hurban and Al-Ostad, 2009, Alkandari and Moein, 2018, Alshammari, 2018, Al-Shammari, 2013, Bourasli, 2013, Bu-Olayan and Thomas, 2011, Bu-Olayan and Thomas, 2010b, Engelbrecht et al, 2009b, Kuśmierczyk-Michulec and Bourgouin, 2018, Li et al, 2020, Nasrallah et al, 2003, Yassin, 2011, Yassin et al, 2018a, Zaki et al, 2017.…”
Section: Non-epidemiological Studiesmentioning
confidence: 99%